Does Incorporation of the Dorsal Cutaneous Branch of the Proper Digital Nerve in Anterograde Neurovascular Island Flap Improve Outcomes? Results of A Retrospective Case Series - Hashmi, Pervaiz M.; Musaddique, Abeer; Ali, Muhammad; Khan, Muhammad A.A.; Khan, Muhammad Z.N.; Zahid, Marij (Archives of Plastic Surgery, 2025)
Fingertip injuries present a challenge for surgeons. Factors such as appearance, sensation, and grip strength influence the choice of procedure. The neurovascular island (NVI) flap is commonly used due to its reliability and favorable results. However, it can lead to reduced sensation and a limited range of motion, which are significant concerns.This study analyzed 56 adult patients with 66 finger injuries treated with a modified NVI flap by a single surgeon. The flap is based on branches of the proper digital artery to the volar and dorsal skin, including two nerves in the resected flap. The FIOS score was used to assess long-term flap outcomes at follow-up. Patients with thumb injuries, incomplete records, or loss of follow-up were excluded.The study found that NVI flaps had a survival rate of 98%. Post-surgery, the patients' outcomes were assessed using the FIOS score, with 61 cases rated as “excellent,” 4 as “good,” and 1 as “fair.” During long-term follow-up, none of the patients experienced cold intolerance or sensory abnormalities, which is attributed to the inclusion of the dorsal cutaneous nerve in the flap.In conclusion, the NVI flap procedure proved to be a reliable method for reconstructing fingertip pulp loss, offering long-term satisfactory outcomes. It provided good coverage with preserved sensation, dexterity, and preservation of finger length, meeting the patients' cosmetic expectations.
Keywords: neurovascular island flap; fingertip injuries; anterograde flap; pulp loss; fingertip injuries